CYP3A5 genotypes affect tacrolimus pharmacokinetics and infectious complications in Chinese pediatric liver transplant patients. (20th January 2014) - Xue, Feng; Han, Longzhi; Chen, Yikuan; Xi, Zhifeng; Li, Qigen; Xu, Ning; Xia, Yun; Streicher, Katie; Zhang, Jianjun; Xia, Qiang
Abstract Little information is available regarding the impact of cytochrome P450 (CYP) 3A5 on the metabolism of TAC in infant LTx. Therefore, the CYP3A5 genotype of Chinese pediatric recipients (intestine) as well as donors (graft liver) was performed for the purpose of establishing an optimal dosage regimen in children. Sixty‐four patients were divided according to CYP3A5 genotype (expression of *1 allele: EX and NEX) for each recipient (R) and donor (D), EX‐R/EX‐D (n = 21), EX‐R/NEX‐D (n = 8), NEX‐R/EX‐D (n = 8) and NEX‐R/NEX‐D (n = 27). Results indicated that initial TAC daily dose requirement was higher among EX‐R/EX‐D children compared with those who did not express CYP3A5 (0.28 ± 0.10 vs. 0.19 ± 0.08 mg/kg/day, p < 0.01). CYP3A5 expression contributed an overall of 38.35% to its C/D ratios, and graft liver was a key determinant. Additionally, the EX‐R/EX‐D group showed significantly higher incidence of infectious complications, lower immune response and was an independent risk factor for the development of infections (odds ratio 3.86, p = 0.025). Donor CYP3A5 expression partially explains TAC dose requirement, the effect of CYP3A5 variation may influence clinical outcomes; therefore, monitoring immune response may be important for preventing risks associated with under‐ and over‐immunosuppression.